Making a beta barrel: Assembly of Outer Membrane Proteins in Gram negative bacteria - Rigel, Nathan W. (2012)
The outer membrane (OM) of Gram negative bacteria is an essential organelle that serves as a selective permeability barrier by keeping toxic compounds out of the cell while allowing vital nutrients in. How the OM and its constituent lipid and protein components are assembled remains an area of active research. In this review, we describe our current understanding of how outer membrane proteins (OMPs) are delivered to and then assembled in the OM of the model Gram-negative organism Escherichia coli.